The Logical Semantics of Conjunctions in Kurdish Language: Propostion, Logic, Meaning, Logical Meaning, Coordinate Conjunctions, Subordinate Conjunctions - Bayan Mala Hamadameen; Sabah Rashed Qader (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
This study is entitled "The Logical Semantic of Conjunctions in Kurdish Language". Logic, which is a significant branch of meaning, has entered language to interpret meaning. The core of this interpretation is the laws of thought and perception. The logical perception is the map of a set of laws and logical principles which are applied by the elements of language. The conjunctions, as language elements belonging to closed class words, have little meaning. The findings of the current study focus on the semantic and logical aspects of the conjunctions, as well as presenting the coordinate and subordinate conjunctions in terms of some of the logical laws in complex sentences. That is, this study is an attempt to present coordinate and subordinate conjunctions within the framework of meaning and logic.